Sources of strain between physicians and social workers: Implications for social workers in health care settings - Mizrahi, T.; Abramson, J. (Social Work in Health Care, 1985)
This paper analyzes the sources of strain between the professions of medicine and social work. The two professions are compared in relation to (1) the organization and socialization process of professional training; (2) perspectives on patient care, illness and role of the health care professional; (3) attitudes toward knowledge and data; (4) attitudes toward and preparation for teamwork; (5) perspectives on the role of the patient; (6) perceptions of social work’s function. © 1985 Taylor & Francis Group, LLC.
Keywords: Attitude of Health Personnel; Human; Internship and Residency; Interprofessional Relations; Medical Staff, Hospital; Patient Advocacy; Professional-Patient Relations; Role; Sick Role; Social Perception; Social Work; Socialization; dept.swk; human; organization and management; physician; psychological aspect; short survey; social aspect; social worker; training; united states